2011
DOI: 10.1590/s2179-64912011000100010
|View full text |Cite
|
Sign up to set email alerts
|

Verificação da efetividade de uma ação educativa sobre proteção auditiva para trabalhadores expostos a ruído

Abstract: Effectiveness verification of an educational program on hearing protection for noise-exposed workers Verificação da efetividade de uma ação educativa sobre proteção auditiva para trabalhadores expostos a ruído ABSTRACT Purpose: To verify the effectiveness of an educational action in the form of training, emphasizing the importance of hearing protection for workers exposed to occupational noise. Me thods: The study included 78 male individuals. All participants answered a questionnaire before they were submitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
2
7
1
9
Order By: Relevance
“…The greatest difficulties of the workers verified in Questionnaire A, with mean scores <3 (inappropriate), occurred in the following themes: Intention of preventive behavior (question 17), Self-efficacy of hearing protection use (questions 9 and 12), Habits harmful to hearing (questions 23 and 24), Knowledge about the effects of noise on health and hearing (questions 28, 29, and 31), Knowledge about hearing diagnosis (questions 33 and 34), and Knowledge about actions of the Hearing Preservation Program (HPP) (questions 35 and 36). Other studies that analyzed workers' knowledge regarding prevention of hearing loss corroborate the findings of this research (12,(25)(26)(27) . For some authors, when noise is not perceived as a harmful environmental factor, little will be done to avoid exposure and its consequences, such as NIHL (6,22,25) .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The greatest difficulties of the workers verified in Questionnaire A, with mean scores <3 (inappropriate), occurred in the following themes: Intention of preventive behavior (question 17), Self-efficacy of hearing protection use (questions 9 and 12), Habits harmful to hearing (questions 23 and 24), Knowledge about the effects of noise on health and hearing (questions 28, 29, and 31), Knowledge about hearing diagnosis (questions 33 and 34), and Knowledge about actions of the Hearing Preservation Program (HPP) (questions 35 and 36). Other studies that analyzed workers' knowledge regarding prevention of hearing loss corroborate the findings of this research (12,(25)(26)(27) . For some authors, when noise is not perceived as a harmful environmental factor, little will be done to avoid exposure and its consequences, such as NIHL (6,22,25) .…”
Section: Discussionsupporting
confidence: 87%
“…Compliance with legislation regarding the performance of audiometry has not always occurred (3) in spite of its importance, because auditory monitoring is fundamental to assess prevention actions (4) . Other studies have also observed an increase in workers' knowledge about preservation of hearing at work after interventions, but with educational strategies and approaches different from that developed in the present study, evidencing percentage changes smaller than those found here (6)(7)(8)11,27,28) . In the USA, a study on educational intervention was conducted with 176 construction workers aiming to increase the use of HPDs.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…These normative changes also promoted more and experiences about his work. This questions if shared collectively, can interfere extraordinarily on the labor environment changing 25,26 . The level of education has been related in literature as an important factor for the success of the educational actions.…”
Section: Discussionmentioning
confidence: 99%
“…Where it is not possible to reduce noise in the sound source, it is necessary the use of protectors. A recent study has shown effectiveness in educational activities training on the use of protectors to employees exposed to occupational noise, if well implemented 18 .…”
Section: Discussionmentioning
confidence: 99%